Impact of Non-Performing Assets on Indian Economy - Sen, Preeti Rani (Journal of Commerce and Trade, 2019)
Financial intermediation by banks is an engine of growth because they cause money to be circulated in the economy by seeking deposits from those who have surplus and lend for investment activity. It has a multiplier effect in the economy! Borrowing leads to creation of demand for productive resources and increases the income level of those who supply goods and services. Expenditure of one is income of the t other. This leads to higher GDP and faster productive growth. Contraction in lending has opposite effect and growth falters. One major reason for muted credit growth is fast accretion of Non Performing Assets (NPAs) on banks' balance sheets. Roughly 72 per cent of market share of outstanding credit of SCBs (Scheduled Commercial Banks) is of PSBs. Meteoric rise of NPAs from Sept 15 had its genesis in rapid credit growth of banks during the preceding years say from 2008 onwards. During the period of 2008 to 2014 gross advances of public sector banks grew from Rs. 18 lakh crores to Rs. 54 lakh crores and by September 17 this figure was Rs. 55.01 lakh crores. No wonder that the share of sticky assets of government owned banks in this pile of bad loan is almost 90 per cent. Classification-JEL : A 14, E 44, E 58